Perceptions of Weight and Health Practices in Hispanic Children: A Mixed-Methods Study - Byron Alexander Foster; Daniel Hale (International Journal of Pediatrics)
Background. Perception of weight by parents of obese children may be associated with willingness to engage in behavior change. The relationship between parents’ perception of their child’s weight and their health beliefs and practices is poorly understood, especially among the Hispanic population which experiences disparities in childhood obesity. This study sought to explore the relationship between perceptions of weight and health beliefs and practices in a Hispanic population. Methods. A cross-sectional, mixed-methods approach was used with semistructured interviews conducted with parent-child (2–5 years old) dyads in a primarily Hispanic, low-income population. Parents were queried on their perceptions of their child’s health, health practices, activities, behaviors, and beliefs. A grounded theory approach was used to analyze participants’ discussion of health practices and behaviors. Results. Forty parent-child dyads completed the interview. Most (58%) of the parents of overweight and obese children misclassified their child’s weight status. The qualitative analysis showed that accurate perception of weight was associated with internal motivation and more concrete ideas of what healthy meant for their child. Conclusions. The qualitative data suggest there may be populations at different stages of readiness for change among parents of overweight and obese children, incorporating this understanding should be considered for interventions.